AAPM Task Group 198 Report: An implementation guide for TG 142 quality assurance of medical accelerators. Issue 10 (11th August 2021) - Hanley, Joseph; Dresser, Sean; Simon, William; Flynn, Ryan; Klein, Eric E.; Letourneau, Daniel; Liu, Chihray; Yin, Fang‐Fang; Arjomandy, Bijan; Ma, Lijun; Aguirre, Francisco; Jones, Jimmy; et al.
Abstract : The charges on this task group (TG) were as follows: (a) provide specific procedural guidelines for performing the tests recommended in TG 142; (b) provide estimate of the range of time, appropriate personnel, and qualifications necessary to complete the tests in TG 142; and (c) provide sample daily, weekly, monthly, or annual quality assurance (QA) forms. Many of the guidelines in this report are drawn from the literature and are included in the references. When literature was not available, specific test methods reflect the experiences of the TG members (e.g., a test method for door interlock is self‐evident with no literature necessary). In other cases, the technology is so new that no literature for test methods was available. Given broad clinical adaptation of volumetric modulated arc therapy (VMAT), which is not a specific topic of TG 142, several tests and criteria specific to VMAT were added.